PENGARUH STRUKTUR MODAL, KEPUTUSAN INVESTASI, LIKUIDITAS TERHADAP NILAI PERUSAHAAN MELALUI KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2020-2023 - Agung Dwi Rianto; Mohammad Yahya Arief; Ida Subaida (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The objective of this study is to determine the effect of capital structure, investment decisions, and liquidity on firm value through dividend policy as an intervening variable in food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. The sampling technique used in this study was purposive sampling, with 38 companies selected. Data analysis and hypothesis testing in this study used the Partial Least Squares Structural Equation Model (PLS-SEM). The results show that capital structure has a significant positive effect on dividend policy, investment decisions have a significant positive effect on dividend policy, liquidity has a significant negative effect on dividend policy, capital structure has a positive but insignificant effect on firm value, investment decisions have a significant positive effect on firm value, liquidity has a positive but insignificant effect on dividend policy, dividend policy has a significant positive effect on firm value, and capital structure has a significant positive effect on firm value through Dividend policy and investment decisions have a positive but insignificant effect on firm value through dividend policy. Liquidity has a negative but insignificant effect on firm value through dividend policy.